Operating temperature effect on the thin film solar cell efficiency - Zaitsev, R. V.; Kirichenko, M. V.; Khrypunov, G. S.; Radoguz, S. A.; Khrypunov, M. G.; Prokopenko, D. S.; Zaitseva, L. V. (Сумський державний університет, 2019)
The made research results of the dependence of the film photovoltaic converter efficiency on their operating temperature and their comparison are considered in the paper. The physical mechanisms of temperature influence analysis on output, diode and electronic parameters of photovoltaic converters were conducted. The output parameters determination of the flexible photovoltaic converters was carried out by measurement of light current-voltage characteristics by using illuminator based on powerful semiconductor LEDs with different colors for simulated radiation which is close to the standard ground and ultraviolet solar spectrum. For ensuring effective non-destructive switching of the test specimens of the flexible PVC based on cadmium telluride to the measurement circle, the special contact device was developed and used. The main feature of contact device is four separate vertically moving metal probes in form of semi spheres with polished surfaces, which makes it impossible to puncture the PVC electrodes. These probes have possibility of individual positioning of each probe that is carried out with the help of a hard rotary console of variable length attached to the body and can be pressed with a given effort without impact on the frontal and any rear electrodes of the PVC experiments. The efficiency temperature coefficients of the photovoltaic converter, which make up for devices with a CdTe of 0.14 %/C, CuInSe2 – 0.36 %/C, amorphous silicon - 0.21 %/C were obtained. The analytical processing and analysis of the light diode characteristic effect on the PVC efficiency based on the CdTe showed that the temperature stability of their efficiency is ensured by the diode current density, the incision of which increases by 50 % from 1.9·10 – 9 A to 2.7·10 – 9 A with the temperature rise from 20 °С to 50 °С. At the same time, it has been established for PVC on the CuInSe and amorphous silicon base that the decrease of short circuit current density, open circuit voltage and fill factor of current-voltage characteristics plays the main role in efficiency reduction with rising temperature.

У роботі розглянуто результати дослідження залежності ефективності плівкових фотоелектричних перетворювачів від їх робочої температури та проведено їх порівняння. Приведено аналіз фізичних механізмів впливу температури на вихідні, діодні та електронні параметри фотоелектричних перетворювачів. Визначення вихідних параметрів гнучких фотоелектричних перетворювачів здійснювалося за допомогою вимірювання світлових вольт-амперних характеристик за допомогою освітлювача на основі потужних напівпровідникових світлодіодів різного кольору для імітаційного випромінювання, характерного для стандартного наземного спектра сонячного світла. Для забезпечення ефективного неруйнівного контакту випробувальних зразків гнучких елементів на основі телуриду кадмію до кола вимірювання розроблено і використано спеціальний контактний пристрій. Головною особливістю контактного пристрою є чотири роздільних вертикально рухомих металевих зонда у вигляді напівсфер з полірованими поверхнями, що унеможливлює проколювання плівкових електродів. Дані зонди мають можливість індивідуального позиціонування кожного зонда, що здійснюється за допомогою твердої поворотної консолі змінної довжини, прикріпленої до корпусу. Отримано коефіцієнти зниження ефективності від робочої температури фотоелектричного перетворювача, що складають для пристроїв на основі CdTe – 0.14 %/C, для CuInSe₂ – 0.36%/C, для аморфного кремнію – 0.21 %/C. Аналітична обробка та аналіз впливу світлових діодних характеристик на ефективність приладів на основі CdTe показали, що температурна стабільність їх ефективності забезпечується стабільністю густини діодного струму насичення, величина якого збільшується на 50 % з 1.9·10 – 9 А до 2.7·10 – 9 А з підвищенням температури від 20 °С до 50 °С. В той же час для приладів на основі CuInSe₂ та аморфного кремнію встановлено, що основну роль у зниженні ефективності при підвищенні температури має зменшення густини струму короткого замикання, напруги холостого ходу та коефіцієнта заповнення вольт-амперних характеристик.
Вплив робочої температури на ефективність тонкоплівкових сонячних елементів
Keywords: photovoltaic converters; solar cells; thin films; efficiency; diode parameters; working temperature; фотоелектричні перетворювачі; тонкі плівки; діодні параметри